Water adsorption on the surface of Ni‐ and Co‐based layer‐structured cathode materials for lithium‐ion batteries. Issue 14 (2nd February 2018) - Kim, Yongseon
Abstract: Ni‐based layer‐structured cathode materials are more vulnerable to moisture than conventional LiCoO2 cathodes, adsorbing more water and easily forming LiOH on the surface. This study investigated the moisture adsorption mechanism on the surface of layer‐structured cathodes. The behavior of water molecules on LiCoO2 and LiNiO2 surfaces were simulated and the structural and chemical changes during the adsorption process were analyzed by first‐principles methods. It was found that the adsorption occurs via two types of mechanism: one involving ionic interactions between Li on the crystal surface and O in the adsorbate, and the other involving covalent bonding between the transition metal (TM) on the surface and O in the adsorbate, which restores the coordination of the TM by recovering its broken bonds. The difference between the water adsorption behaviors of Ni‐based and Co‐based layer‐structured cathodes was found to be mainly due to the ionic‐interaction‐driven adsorption on the (003) surface. Abstract : Ni‐based layer‐structured cathode materials are more vulnerable to moisture than conventional LiCoO2 cathodes in lithium‐ion batteries. This study investigates the moisture adsorption mechanism on the surface of layer‐structured cathodes, by comparing the behavior of water molecules on LiCoO2 and LiNiO2 surfaces. The structural and chemical changes during the adsorption process are analyzed by first‐principles methods.